PENGARUH JUMLAH PENDUDUK, UMR, DAN TPT TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Aprilya, Isna; Juliprijanto, Whinarko (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study discusses the analysis of the Influence of Population, UMR, and TPT that affect Economic Growth in Indonesia in 1990-2020. The data used are time series data sourced from the World Bank and BPS in this study the method used is ECM (Error Correction Model). Before performing the ECM test, the data must be tested for stationarity and cointegration, then after managing the data using the ECM method, the Classic Assumption Test consists of: Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, and Normality Test. The results of this study indicate that the regional minimum wage and open unemployment have a significant effect on economic growth in Indonesia in the short and long term. While the population has no significant effect on population growth.